KCNQ Modulators Reveal a Key Role for KCNQ Potassium Channels in Regulating the Tone of Rat Pulmonary Artery Smooth Muscle - Joshi, Shreena; Sedivy, Vojtech; Hodyc, Daniel; Herget, Jan; Gurney, Alison M. (The Journal of pharmacology and experimental therapeutics, 2009)
Potassium channels are central to the regulation of pulmonary vascular tone. The smooth muscle cells of pulmonary artery display a background K+ conductance with biophysical properties resembling those of KCNQ (KV7) potassium channels. Therefore, we investigated the expression and functional role of KCNQ channels in pulmonary artery. The effects of selective KCNQ channel modulators were investigated on K+ current and membrane potential in isolated pulmonary artery smooth muscle cells (PASMCs), on the tension developed by intact pulmonary arteries, and on pulmonary arterial pressure in isolated perfused lungs and in vivo. The KCNQ channel blockers, linopirdine and XE991 [10,10-bis(4-pyridinylmethyl)-9(10H)-anthracenone], inhibited the noninactivating background K+ conductance in PASMCs and caused depolarization, vasoconstriction, and raised pulmonary arterial pressure without constricting several systemic arteries or raising systemic pressure. The KCNQ channel openers, retigabine and flupirtine, had the opposite effects. PASMCs were found to express KCNQ4 mRNA, at higher levels than mesenteric artery, along with smaller amounts of KCNQ1 and 5. It is concluded that KCNQ channels, most probably KCNQ4, make an important contribution to the regulation of pulmonary vascular tone, with a greater contribution in pulmonary compared with systemic vessels. The pulmonary vasoconstrictor effect of KCNQ blockers is a potentially serious side effect, but the pulmonary vasodilator effect of the openers may be useful in the treatment of pulmonary hypertension.